The Effect of Entrepreneurship Education on Entrepreneurial Readiness: The Mediating Role of Use of Social Media - Ghozali, Mohammad Syukri Ghozali; Ludi Wishnu Wardana; Nurika Restuningdiah (Social Science Studies, 2025)
Research Aims: The aim of this research is to examine the effect of entrepreneurship education on students' readiness to become entrepreneurs, focusing on the role of social media usage as a mediating factor. This study specifically targets students enrolled in marketing expertise programs at public and private vocational high schools (SMKN and SMKS) in Jombang District, aiming to understand how entrepreneurship education and social media engagement can enhance students' entrepreneurial readiness. Design/methodology/approach: This research uses a quantitative approach with Partial Least Squares structural equation modelling (PLS-SEM) to predict and confirm the given hypothesis. This study uses google form for data collection on students of SMKN & SMKS with Marketing Expertise Program in Jombang Regency. Respondents in this study were 122 respondents from the three schools that were used as research objects. Research Findings: The results of this study indicate that entrepreneurship education does not have a significant influence on entrepreneurial readiness of SMKN & SMKS students with Marketing Expertise Program in Jombang Regency, but the use of social media acts as an important mediator to strengthen entrepreneurship education. Use of social media has a significant positive influence on entrepreneurial readiness. While entrepreneurship education has a significant positive effect on Use of social media. Theoretical Contribution/Originality: This research contributes to the theoretical understanding of how entrepreneurship education impacts students' readiness to become entrepreneurs, highlighting the unique role of social media usage as a mediator. By focusing on students in marketing programs at vocational high schools in Jombang District, this study adds insights into how integrating social media can strengthen the effectiveness of entrepreneurship education. This approach offers a fresh perspective on preparing students for entrepreneurship in a digital age, emphasizing the importance of social media skills in enhancing entrepreneurial readiness.